Optical trapping forces exerted by a pulsed Hermite–Gaussian beam on a dielectric nanosphere - M.A. Shukri; F.M. Thabit (Results in Physics, 2024)
An analytical expression for the optical forces exerted by a pulsed Hermite–Gaussian (HG) beam on a nano-dielectric sphere has been derived. This allows us to investigate how the forces are affected by different beam modes (p,l) and the duration of the light pulse (τ). Our findings demonstrate that these factors significantly influence the strength of the forces, the number of regions where the sphere can be trapped, and the size of these trapping zones. This knowledge paves the way for precise control of these tiny particles with light, potentially leading to improved techniques for trapping and sorting nanoparticles.